A Study on Impact of Smart HRM in Bengaluru Smart City - Mithun R; S, Roopadarshini (MultiTech Publisher, 2023)
Our study aims to examine the role of Smart Human Resource Management (HRM) in the development of Bengaluru Smart City. The objectives of the study are twofold: first, to understand how Smart HRM can contribute to the overall success and development of the city, and second, to analyse the positive and negative impact of smart HRM in Bengaluru Smart City. The research methodology for this study will involve a review of literature on smart HRM and its impact on various HR processes such as recruiting, onboarding, performance management, employee engagement, and training and development. The scope of work in this study will involve conducting surveys and interviews with HR professionals in Bengaluru to understand the current state of smart HRM practices in the city and its impact on employee engagement and retention. The findings of this study will provide valuable insights into the role of smart HRM in the development of a smart city and its potential impact on the workforce. As a part of conclusion of our study we say that Smart HRM has the potential to greatly improve the efficiency and effectiveness of human resource management in Bengaluru Smart City Development initiative, by utilizing technology to automate, streamline HR processes, providing real-time data and analytics, and improving employee engagement and satisfaction.